2014
DOI: 10.1371/journal.pone.0093559
|View full text |Cite
|
Sign up to set email alerts
|

Model-Based Analysis of Costs and Outcomes of Non-Invasive Prenatal Testing for Down’s Syndrome Using Cell Free Fetal DNA in the UK National Health Service

Abstract: BackgroundNon-invasive prenatal testing (NIPT) for Down’s syndrome (DS) using cell free fetal DNA in maternal blood has the potential to dramatically alter the way prenatal screening and diagnosis is delivered. Before NIPT can be implemented into routine practice, information is required on its costs and benefits. We investigated the costs and outcomes of NIPT for DS as contingent testing and as first-line testing compared with the current DS screening programme in the UK National Health Service.MethodsWe used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
118
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 102 publications
(128 citation statements)
references
References 26 publications
7
118
0
3
Order By: Relevance
“…However, these studies focused on NIPT being utilised in a high-risk population only [32], did not include current practice using conventional screening methods as a comparator [33], or did not include secondtrimester ultrasonographic examination in their model [32][33][34][35]. Due to these differences in methods used, results cannot be compared.…”
Section: Commentmentioning
confidence: 99%
“…However, these studies focused on NIPT being utilised in a high-risk population only [32], did not include current practice using conventional screening methods as a comparator [33], or did not include secondtrimester ultrasonographic examination in their model [32][33][34][35]. Due to these differences in methods used, results cannot be compared.…”
Section: Commentmentioning
confidence: 99%
“…Despite the evidence supporting NIPT first-line screening as cost-effective, other published studies have found that the improved clinical benefits of NIPT first-line screening are too costly [31,32]. The assumed cost of NIPT has a significant impact on cost-effectiveness analyses.…”
Section: Discussionmentioning
confidence: 99%
“…While the sensitivity and specificity for the general population is comparable to the high-risk group, the predictive value of the test is lower due to the lower incidence of anomalies. Coupled with the costs of performing sequencing this means it is currently not economically viable to replace primary screening tests by NIPT [102,103]. However, the costs of sequencing continue to decrease, making it possible to offer NIPT to all pregnant women in the near future.…”
Section: Expert Commentary and Five-year Viewmentioning
confidence: 99%